2018
DOI: 10.1136/bcr-2018-224941
|View full text |Cite
|
Sign up to set email alerts
|

Campylobacter jejuniandPseudomonascoinfection in the setting of ulcerative colitis

Abstract: A 66-year-old woman presented with 2 days of fever and severe diarrhoea. She has a history of ulcerative colitis (UC), well controlled with medication. She also has a history of Ehlers-Danlos syndrome, infective endocarditis following aortic valve replacement and pulmonary embolism. She had complained of passing stool with traces of blood about 30 times per day. Stool testing for routine culture and microscopy was done. She was started on ceftriaxone. CT scan revealed thick-walled colon consistent with UC flar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Finally, considering the potential of P. fruticosa as a source of antimicrobial agents (Ristic et al, ), we performed a parallel set of experiments in order to evaluate the effects of P. fruticosa and P. herba‐venti on Gram‐positive and Gram‐negative bacterial strains and fungal species involved in IBDs (Guo et al, ; Iguidbashian et al, ; Trojanowska et al, ; Wang et al, ). Microbiome dysbiosis is an increase in the number of bacteria associated with colon mucosa, alongside a reduction in biodiversity (Kaur, Chen, Luther, & Kao, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, considering the potential of P. fruticosa as a source of antimicrobial agents (Ristic et al, ), we performed a parallel set of experiments in order to evaluate the effects of P. fruticosa and P. herba‐venti on Gram‐positive and Gram‐negative bacterial strains and fungal species involved in IBDs (Guo et al, ; Iguidbashian et al, ; Trojanowska et al, ; Wang et al, ). Microbiome dysbiosis is an increase in the number of bacteria associated with colon mucosa, alongside a reduction in biodiversity (Kaur, Chen, Luther, & Kao, ).…”
Section: Resultsmentioning
confidence: 99%
“…In IBDs, there is a significant reduction in beneficial bacteria, including Firmicutes, Bacteroidetes, Actinobacteria, and Verrucomicrobia, with a concomitant increase in anaerobic bacteria of the family Enterobacteriaceae, playing a pathogenic role in the inflamed colon (Zuo & Ng, ). Despite there still being no identification of causative microorganism in IBDs, multiple studies suggested the involvement of pathogens such as Mycobacterium avium paratuberculosis , Clostridium difficile , and Helicobacter and altered commensals such as adherent‐invasive E. coli (Issa et al, ; Thomson et al, ; Nazareth et al, ; Palmela et al, ), whereas case report studies indicated the inflamed colon as a favorable environment for infection of different opportunistic pathogens, including P. aeruginosa and S. aureus (Bettenworth et al, ; Iguidbashian et al, ). A great deal of interest also emerged as regards the involvement of fungi in colon inflammation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also evaluated the effects of Origanum extracts on pathogen bacteria and fungi strains deeply involved in colon inflammation (Cho & Chae, 2004;Guo et al, 2015;Iguidbashian, Parekh, Kukrety, & Andukuri, 2018;Trojanowska et al, 2010;Wang et al, 2018). Regarding the antibacterial activity, Origanum extracts were particularly effective against S. aureus and to a lesser extent toward S. thyphimurium (Table 5).…”
Section: Pharmacological Studiesmentioning
confidence: 99%
“…In this regard, the proteomic investigation was carried out on a cluster of more than 100 proteins involved in colon cell morphology and metabolism. Finally, the extract antimicrobial activity was studied against E. coli, S. aureus, P. aeruginosa, Candida albicans, and C. tropicalis, which are known to be involved in IBDs [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%